2022
DOI: 10.3390/diagnostics12081831
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Based Pain Assessment Technology in Clinical Application of Real-World Neonatal Blood Sampling

Abstract: Background: Accurate neonatal pain assessment (NPA) is the key to neonatal pain management, yet it is a challenging task for medical staff. This study aimed to analyze the clinical practicability of the artificial intelligence based NPA (AI-NPA) tool for real-world blood sampling. Method: We performed a prospective study to analyze the consistency of the NPA results given by a self-developed automated NPA system and nurses’ on-site NPAs (OS-NPAs) for 232 newborns during blood sampling in neonatal wards, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The results in Table 3 show that compared with the on-site evaluation, the accuracy of the NIPS pain grade given by the VB-NPA with neonatal pain videos captured in a real-world NICU scenario was 96.98%, and the agreement between the two groups was compared, with a kappa value of 0.926 ( p < 0.001), thus indicating that, although the accuracy of VB-NPA was affected by real-world noises in the videos, it was not inferior to OS-NPA. Previous studies have shown that compared to OS-NPA, VB-NPA could significantly reduce the time spent on pain evaluation [ 22 , 23 , 24 , 25 ]. Meanwhile, with the advances in technology and operating equipment, it is easier to video-record painful procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The results in Table 3 show that compared with the on-site evaluation, the accuracy of the NIPS pain grade given by the VB-NPA with neonatal pain videos captured in a real-world NICU scenario was 96.98%, and the agreement between the two groups was compared, with a kappa value of 0.926 ( p < 0.001), thus indicating that, although the accuracy of VB-NPA was affected by real-world noises in the videos, it was not inferior to OS-NPA. Previous studies have shown that compared to OS-NPA, VB-NPA could significantly reduce the time spent on pain evaluation [ 22 , 23 , 24 , 25 ]. Meanwhile, with the advances in technology and operating equipment, it is easier to video-record painful procedures.…”
Section: Discussionmentioning
confidence: 99%
“… Identify the specific signals and patterns from each facial sensor that correlate with the pain stimulus. 34 Cheng, X et al . (2022) / China Artificial Intelligence Based Pain Assessment Technology in Clinical Application of Real-World Neonatal Blood Sampling.…”
Section: Challenging Issuesmentioning
confidence: 99%
“… Tests will be performed in further studies. 34 It was implemented with the client-server model and designed to run on the mobile nursing personal digital assistant device. /Scale: NIPS Own Base (232 newborns with a mean gestational age of 33.93 ± 4.77 weeks).…”
Section: Challenging Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cheng et al (2022), it is provided three approaches to generate explanations: directly from a transparent machine learning algorithm (e.g., Decision Trees), or from an algorithm that creates a post-hoc modelling, or visualisation tool. We benefit from the third approach, using mechanisms external to the main classification model to help describe the decision-making process of it.…”
Section: Explainable Artificial Intelligencementioning
confidence: 99%